2022
DOI: 10.1123/jsr.2020-0247
|View full text |Cite
|
Sign up to set email alerts
|

Instrument-Assisted Soft Tissue Mobilization Forces Applied by Trained Clinicians During a Simulated Treatment

Abstract: Context: Instrument-assisted Soft Tissue Mobilization (IASTM) is a therapeutic intervention used by clinicians to identify and treat myofascial dysfunction or pathology. However, little is known about the amount of force used by clinicians during an IASTM treatment and how it compares to reports of force in the current literature. Objective: To quantify the range of force applied by trained clinicians during a simulated IASTM treatment scenario. Design: Experimental. Setting: University research laboratory. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…Prior reports have indicated that clinicians may not consider or be able to calculate the amount of force being applied during IASTM. 5,6 Clinicians may also not accurately predict the amount of force being produced during IASTM, 17 and optimal force application for IASTM has not been established across pathologies or treatment locations. 11 Our results, however, inform the efforts in this area by providing evidence that IASTM trained clinicians still provide consistent F peak and F mean within a therapeutic range across treatment sessions despite these limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior reports have indicated that clinicians may not consider or be able to calculate the amount of force being applied during IASTM. 5,6 Clinicians may also not accurately predict the amount of force being produced during IASTM, 17 and optimal force application for IASTM has not been established across pathologies or treatment locations. 11 Our results, however, inform the efforts in this area by providing evidence that IASTM trained clinicians still provide consistent F peak and F mean within a therapeutic range across treatment sessions despite these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A convenience sample of 5 licensed athletic trainers who were a subset of a previous study 17 was utilized for this study. Participants were included if they had previously completed at least one professional IASTM training course (Técnica Gávilan ® = 5 and RockBlades ® = 1).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to improve the patient's musculoskeletal dysfunctions, with the help of one or more IASTM, not only improves some functional parameters for the patient but can protect the joints of the operator's/clinician's hand. Recent studies have shown that clinicians who treat myofascial disorders can apply sufficient force to reach the desired tissue depth through the use of IASTM [45,46]. This allows the operator to save the use of the joints of the hand [47].…”
Section: The Significant Advantages Of Using An Iastm In Manual Therapymentioning
confidence: 99%
“…The Técnica Gavilán® instrument Ala has also been used in prior studies. 1,2,7,16 The weight of the instrument is 196g. The Técnica Gavilán® instrument is a stainless-steel tool with a single beveled edge which allows unilateral strokes by the clinician (Figure 2).…”
Section: Instrumentationmentioning
confidence: 99%